Cost Risk and Quality Control Analysis of Nutrition Service Unit Construction in Selayar Islands - Santi Rahmawati; Pio Ranap Tua Naibaho (Universitas Medan Area, 2026)
The construction of Nutrition Service Units (SPPG) is a strategic component of Indonesia’s Free Nutritious Meals Program, requiring effective cost-risk management and quality control to ensure successful project delivery. These challenges become more significant in island regions where transportation constraints, material availability, and unpredictable weather increase project uncertainty. This study aims to analyze cost-risk characteristics, evaluate quality-control performance, identify factors affecting cost deviation, and develop an over-budget prediction model for SPPG construction projects in the Selayar Islands. A quantitative research design was employed using 88 work-item observations representing preparatory, structural, architectural, mechanical-electrical-plumbing, and infrastructure works. Statistical analyses included descriptive statistics, Shapiro–Wilk normality testing, Cronbach's Alpha reliability analysis, correlation analysis, independent sample t-test, one-way ANOVA, multiple linear regression, binary logistic regression, and K-Means clustering. The findings indicate that the overall project cost deviation was −0.42% of the contract value, although 25.0% of work items experienced cost overruns. Work categories significantly influenced cost deviation, whereas construction methods showed no significant effect. Cost risk exhibited a very strong negative relationship with quality-control performance (ρ = −0.918). The proposed statistical framework provides practical support for prioritizing risk control in future SPPG construction projects under island construction conditions.